ESG ratings, executive pay-for-performance sensitivity and within-firm pay gap - Xinze Li; Xi Wang; Zuoxiang Zhao; Qiuyun Zhao (Humanities & Social Sciences Communications)
Abstract Addressing the factors that contribute to within-firm pay disparities has become increasingly urgent in light of growing global income inequality. This study explores the effect of corporate ESG (Environmental, Social, and Governance) ratings on pay gaps using data from Chinese-listed companies between 2017 and 2021. The findings reveal that higher ESG ratings are associated with a significant widening of the pay gap between executives and ordinary employees, primarily driven by an increase in executive pay-for-performance sensitivity. Governance (G) emerges as the key factor amplifying this sensitivity. Heterogeneity analysis shows that this effect is particularly pronounced in non-state-owned and large-scale firms. Additionally, the impact is evident across various firms in traditional and highly competitive industries. These results suggest that regulators should pay closer attention to internal income distribution when promoting ESG principles, as a way to mitigate widening income inequality within firms.